Comparison of Newly Graduated Nurses' and Doctors' Opinions About Spiritual Care and Their Emotional Intelligence Levels - Sabanciogullari, Selma (Journal of religion and health, 2020)
The study has been conducted to compare newly graduated nurses' and doctors' opinions about spiritual care and their emotional intelligence levels. Descriptive study’s sample consisted of 50 nurses and 50 doctors who graduated from a university's medical faculty and health faculty recently. Data were collected by Personal Information Form, Spirituality and Spiritual Care Rating Scale, and Schutte Emotional Intelligence Scale. Emotional intelligence (t = 3.42, p = 0.001) and spirituality and spiritual care detection levels (t = 3.63, p = 0.000) of nurses were found to be higher than those of doctors, and the difference between them was statistically significant. 84% of nurses and 50% of doctors stated that the spiritual care is necessary. While most of the nurses reported that they got training on spiritual care, only 32% of doctors said they did get.